2018
DOI: 10.2147/copd.s173664
|View full text |Cite|
|
Sign up to set email alerts
|

What is the impact of GOLD 2017 recommendations in primary care? – a descriptive study of patient classifications, treatment burden and costs

Abstract: PurposeThe changes in grading of disease severity and treatment recommendations for patients with COPD in the 2017 GOLD strategy may present an opportunity for reducing treatment burden for the patients and costs to the health care system. The aim of this study was to assess the implications of the GOLD 2017 grading system in terms of change in distribution across GOLD groups A–D for existing patients in UK primary care and estimate the potential cost savings of implementing GOLD 2017 treatment recommendations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 20 publications
1
22
0
Order By: Relevance
“…Therefore, it is anticipated that the newer GOLD classification will decrease the therapeutic burden of these patients without affecting their clinical outcomes. Application of GOLD 2017 criteria in a cross-sectional study involving over 19 000 patients from the UK Clinical Practice Research Datalink (CPRD) led to reclassification of 37% of all participants from groups C and D (according to GOLD 2013) to groups A and B [ 47 , 48 ]. Only 16% of all patients with COPD were classified as GOLD groups C or D according to GOLD 2017, compared to 54% according to GOLD 2013 [ 47 , 48 ].…”
Section: Copdmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is anticipated that the newer GOLD classification will decrease the therapeutic burden of these patients without affecting their clinical outcomes. Application of GOLD 2017 criteria in a cross-sectional study involving over 19 000 patients from the UK Clinical Practice Research Datalink (CPRD) led to reclassification of 37% of all participants from groups C and D (according to GOLD 2013) to groups A and B [ 47 , 48 ]. Only 16% of all patients with COPD were classified as GOLD groups C or D according to GOLD 2017, compared to 54% according to GOLD 2013 [ 47 , 48 ].…”
Section: Copdmentioning
confidence: 99%
“…Application of GOLD 2017 criteria in a cross-sectional study involving over 19 000 patients from the UK Clinical Practice Research Datalink (CPRD) led to reclassification of 37% of all participants from groups C and D (according to GOLD 2013) to groups A and B [ 47 , 48 ]. Only 16% of all patients with COPD were classified as GOLD groups C or D according to GOLD 2017, compared to 54% according to GOLD 2013 [ 47 , 48 ]. A cross-sectional study in Poland involving 2597 patients with COPD, as identified by primary care physicians, confirmed that the application of GOLD 2017 leads to a decrease in patients allocated to GOLD groups C and D by 60% [ 49 ].…”
Section: Copdmentioning
confidence: 99%
“…The expense of inhaler prescriptions skyrocketed after the ban of chlorofluorocarbon propellants in 2008, virtually eliminating all the generic inhalers from the market. The changes in the global initiative for chronic obstructive lung disease (GOLD) guidelines in 2017 [6] and the global initiative for asthma (GINA) guidelines in 2019 [7] are estimated to change the type and cost of inhaler prescriptions significantly.…”
Section: Introductionmentioning
confidence: 99%
“…Chronic obstructive pulmonary disease (COPD), a leading cause of death, disability and health-related expenditure globally, is characterised by chronic debilitating respiratory symptoms and acute exacerbations, that drive the adverse outcomes of the disease. [1][2][3][4] Both stable COPD and exacerbations are complex and heterogeneous, meaning that several distinct mechanistic pathways contribute to their development and progression. 5 6 While some of these pathways are well established, our understanding of the pivotal strengths and limitations of this study ► A holistic approach to a clinically pertinent question that could pump-prime clinical and translational research and facilitate the introduction of precision medicine interventions both for stable chronic obstructive pulmonary disease and exacerbations.…”
Section: Introductionmentioning
confidence: 99%